Development and Implementation of the How to Talk to Your Doctor HANDbook Health Literacy Program in Rural Counties - Lisa Washburn; Kristie B. Hadden; Latrina Y. Prince; Charleen McNeill; Zola Moon (SLACK Incorporated, 2019)
BACKGROUND: Improvements in health literacy are unlikely without intervention in community settings. However, interventions appropriate for delivery in these settings are lacking, limiting reach to rural adults who are disproportionately affected by low health literacy and poor health outcomes. The How to Talk to Your Doctor (HTTTYD) HANDbook Program was developed through a research-practice partnership to educate rural residents to effectively advocate and participate in their own health care. BRIEF DESCRIPTION OF ACTIVITY: We describe development of the HTTTYD HANDbook Program delivered through the Cooperative Extension Service to educate adults who are eligible for Medicaid and have low health literacy. HTTTYD HANDbook implementation is described using the RE-AIM (reach, effectiveness, adoption, implementation, and maintenance) framework (and specifically the reach, adoption, implementation, and maintenance dimensions). IMPLEMENTATION: The HTTTYD HANDbook was developed using health literacy best practices with user-centered design, and it was field tested with community members with varying levels of health literacy. Reach, adoption, implementation, and maintenance of the HTTTYD HANDbook were assessed by tracking distribution of HTTTYD HANDbook Program materials, return submission of evaluation and tracking instruments, adherence to program and data collection/submission protocols, and program continuation. RESULTS: Overall reach into the population was 6 per 10,000; about 25% were Medicaid recipients and 28.2% had low health literacy. Most participants were age 65 years or older. Of the 72 counties with program access, 52.7% requested HTTTYD HANDbook Program materials; 31% adopted the program, but only 30% of these counties adhered to program implementation and data collection protocols. Reach and adoption were higher among rural counties, and rural counties were more likely than nonrural counties to maintain the HTTTYD HANDbook Program. LESSONS LEARNED: The HTTTYD HANDbook Program addresses barriers to engagement in patient-provider communication for rural, low-income community members. Programs can be implemented in community settings through established local organizations, such as county extension offices, to increase access for rural adults. Implementation barriers included staff turnover and transportation of program materials. Online facilitator training availability had little impact on adherence to program protocols. Organizational context and established procedures for program delivery and evaluation should be considered in adoption decisions and integrated into implementation protocols.